Bilateral suboccipital approach for a giant vertebral artery aneurysm. (November 2017) - Murai, Yasuo; Yamada, Toshimasa; Ishisaka, Eitaro; Sato, Shun; Matano, Fumihiro; Morita, Akio
Highlights: Giant thrombosed aneurysms of the tortuous vertebral artery are difficult to treat. The distal and proximal of the giant aneurysm exist on both sides of the midline. We believe a bilateral approach from both sides of the brainstem is useful. Abstract: Giant thrombosed aneurysms of the vertebral artery (VA) are difficult to treat. Moreover, marked tortuosity of the parent VA complicates determination of the surgical approach. We report the case of a 71-year-old male patient who presented with gait disturbance. Magnetic resonance imaging revealed a giant thrombosed aneurysm of approximately 4 cm in diameter located in the ventral region and to the right of the medulla oblongata. Computed tomography angiography showed that the right VA had extreme tortuosity, and that the VA union was in contact with the left 7th and 8th cranial nerves. Given that the aneurysm was thrombosed and causing a mass effect, we sought to trap it. In this case, because of the tortuous VA, intravascular team considered intravascular therapy to be too difficult. We made a question mark-shaped skin incision and used a wide bilateral suboccipital approach. The VA proximal to the aneurysm was occluded with an aneurysm clip using an approach from the right of the brainstem, while the VA distal to the aneurysm was occluded using a lateral suboccipital approach. When the VA and basilar artery are atherosclerotic and extremely tortuous, the distal and proximal aspects of the aneurysm can exist on both sides of the midline. In difficult cases such as that reported here, in which a giant VA aneurysm exceeded the midline of the anterior surface of the medulla, we believe that it is useful to employ a bilateral approach from both sides of the brainstem.